Difference of a different kind : Jewish constructions of race during the long eighteenth century - Idelson-Shein, Iris (Jewish culture and contexts., 2014)
The eighteenth century has long been considered a formative period in the history of European racial identity. Difference of a Different Kind offers a new exploration of the ways Jewish authors confronted notions of race that began to pervade European ideology and adapted them to construct their own identity.